Deradicalising Deportees : Vacuum in Coordination? - Anindya, Chaula Rininta (2018)
The absence of coordination among stakeholders in Indonesia to handle the influx of deportees is creating a vacuum calling out to be plugged. Otherwise the deportees might encounter obstacles to reintegrate into the society.